(untitled) (KULT_online, 2021)
TWENTYFORTY. Utopias for a Digital Society (ed. Benedikt Fecher) comprises thirteen pieces of creative fiction looking at problems that arise in an ever more digitized world. Set in 2040 – sometimes utopian, sometimes dystopian – the texts reflect present problems in the relationship between the digital and the social. Written and published just before the COVID-19 pandemic, the book projects a future that now feels stilted. As an attempt by academics to think differently, shift genres and expand audiences, it is an interesting, if unlikely, experiment in imagining utopia.